Polymerization-induced self-assembly for the fabrication of polymeric nano-objects with enhanced structural stability by cross-linking - Zhang, Wen-Jian; Kadirkhanov, Jamshid; Wang, Chang-Hui; Ding, Sheng-Gang; Hong, Chun-Yan; Wang, Fei; You, Ye-Zi (Polymer chemistry, 2020)
Polymerization-induced self-assembly (PISA) has been established as a robust strategy to synthesize block copolymer nano-objects with various morphologies, sizes, and surface chemistry, which greatly enlarges the library of functional nano-objects for further applications. The structural stability of nano-objects is an important concern when they are used in drug delivery, nanoreactors, Pickering emulsifiers, etc . Generally, chemical cross-linking via either post-polymerization or in situ cross-linking strategies has been demonstrated to be a viable strategy to improve the structural stability of the nano-objects. In this review, we focus on the PISA-generated nano-objects with enhanced structural stability via either post-polymerization or in situ cross-linking strategies and their applications. This review discusses the strategies of core-cross-linking in most of the PISA literatures (including post-polymerization cross-linking, photo-cross-linking and in situ cross-linking) and the applications of the cross-linked nano-objects.